A KRT6A mutation p.Ile462Asn in a Chinese family with pachyonychia congenita, and identification of maternal mosaicism: a case report - Yue Li; Yumeng Wang; Yan Ming; Pan Chaolan; Zhang Jia; Ni Cheng; Cao Qiaoyu; Ming Li; Xu Tianyi (BMC, 2021)
Abstract Background Pachyonychia congenita (PC, OMIM #167200, #167210, #615726, #615728, and #615735) is a rare autosomal dominant disorder caused by keratin gene mutations in KRT6A,KRT6B,KRT6C,KRT16 or KRT17. It is characterized with nail dystrophy and palmoplantar keratoderma (PPK). The most prominent manifestation is plantar pain. This is a further unusual case of parental mosaicism in PC. Although very rare, germ cell mosaicism should be considered when providing genetic counselling for unaffected parents of a child with PC. Case presentation We report the case of a 5-year-old boy with thickening nails and oral leukokeratosis at birth. He began to develop palmoplantar keratoderma at 2 years old and his sister has similar clinical manifestation characterized with nail discoloration and thickening. A previously reported heterozygous mutation, p.Ile462Asn, was identified in KRT6A in the proband and his affected sister. SNaPshot sequencing revealed mosaicism at a level of 2.5% and 4.7% in DNA from blood and hair bulbs from the unaffected mother. HiSeq deep sequencing demonstrated low-grade mosaicism in the patient's younger sister and parents. Conclusion These findings indicate the ability of WES and SNaPshot sequencing to detect low-frequency mosaic mutations. Although very rare, germinal mosaicism should be considered when genetic counseling is given to families with presumed spontaneous cases of PC.